Connective tissue growth factor regulates interneuron survival and information processing in the olfactory bulb - Khodosevich, Konstantin; Lazarini, Françoise; Engelhardt, Jakob von; Kaneko, Hiroshi; Lledo, Pierre-Marie; Monyer, Hannah (Neuron, 2013)
Neurogenesis underlies plastic changes in defined neuronal circuits in the postnatal and adult brain. Here we identify connective tissue growth factor (CTGF) as a critical factor in the mouse olfactory bulb (OB) in determining the efficiency of incorporation of postnatally born inhibitory neurons, thus gating the output of glomeruli, the first relay station of olfactory processing in the brain. In the OB, CTGF expression was restricted to prenatally born external tufted cells. CTGF enhanced the proapoptotic activity of glial-derived TGF-β2, decreasing the survival of periglomerular inhibitory neurons. Changes in CTGF expression levels in the OB led to modifications in local neuronal circuitry and olfactory behaviors. We show that the odorant-specific recruitment of distinct glomeruli resulted in enhanced local CTGF expression levels in the activated glomeruli. Collectively our data reveal a molecular mechanism controlling the survival of defined postnatally born neurons, thus adapting neuronal integration to the sensory experiences.
Gesehen am 29.04.2021